2014
DOI: 10.1024/0300-9831/a000204
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D, Parathormone and Associated Minerals among Students in Zagazig District, Sharkia Governorate, Egypt

Abstract: Our findings revealed that hypovitaminosis D is a prevalent health problem in adolescents, especially girls, who were at higher risk, and increased age and sun exposure improved vitamin D status among the studied group. There is therefore a need to consider vitamin D supplementation for school children together with increased awareness through a health education program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 0 publications
4
3
0
Order By: Relevance
“…Also, Haq and colleagues [ 28 ] and Al Anouti and colleagues studies done in Emirates (25° 16’ N and 55° 17′ E) [ 29 ] reported a high prevalence of vitamin D deficiency among healthy Emirati adults. The same thing has been proved in Egypt by El Badawy and colleagues’ study [ 30 ].…”
Section: Discussionsupporting
confidence: 73%
“…Also, Haq and colleagues [ 28 ] and Al Anouti and colleagues studies done in Emirates (25° 16’ N and 55° 17′ E) [ 29 ] reported a high prevalence of vitamin D deficiency among healthy Emirati adults. The same thing has been proved in Egypt by El Badawy and colleagues’ study [ 30 ].…”
Section: Discussionsupporting
confidence: 73%
“…Our work shows an inverse association between serum 25OHD and PTH. Other authors have observed this correlation [19][20][21] .…”
Section: Discussionsupporting
confidence: 57%
“…Overall, 53.6 million adults presented both osteoporosis and low bone mass, accounting for about 54% of the American population 50 years of age and older 3 ) . In the case of Egypt, various research has revealed that osteopenia and osteoporosis affected postmenopausal women in proportions of 53.9% and 28.4%, respectively 4 , 5 ) , while 26% and 21.9% of men were respectively affected by the two diseases 6 ) . Similarly, in Saudi Arabia, about 23% of women with ages between 50 and 70 years old suffered from osteoporosis 7 ) .…”
Section: Introductionmentioning
confidence: 99%